2009
DOI: 10.1007/400_2009_6
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Immune Crosstalk in CNS Diseases

Abstract: Immune cells infiltrate the central nervous system (CNS) in many neurological diseases, with a primary or secondary inflammatory component. In the CNS, immune cells employ shared mediators to promote crosstalk with neuronal cells. The net effect of this neuro-immune crosstalk critically depends on the context of the interaction. It has long been established that inflammatory reactions in the CNS can cause or augment tissue injury in many experimental paradigms. However, emerging evidence suggests that in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 115 publications
2
66
0
1
Order By: Relevance
“…With respect to the role played by central IL-6 in regulating epileptic activity, prior studies demonstrate that IL-6 can stimulate the synthesis of corticotrophin and glucocorticoids, and initiate an anti-inflammatory feedback loop, suggesting a neuroprotective role played by IL-6 [29,30]. Consistent with the findings of prior studies [31][32][33], we have observed increases in the levels of IL-1β, IL-6 and TNF-α in the parietal cortex, hippocampus and amygdala 3 days after KA-induced SE.…”
Section: Discussionsupporting
confidence: 81%
“…With respect to the role played by central IL-6 in regulating epileptic activity, prior studies demonstrate that IL-6 can stimulate the synthesis of corticotrophin and glucocorticoids, and initiate an anti-inflammatory feedback loop, suggesting a neuroprotective role played by IL-6 [29,30]. Consistent with the findings of prior studies [31][32][33], we have observed increases in the levels of IL-1β, IL-6 and TNF-α in the parietal cortex, hippocampus and amygdala 3 days after KA-induced SE.…”
Section: Discussionsupporting
confidence: 81%
“…These processes may be kept in check for the restoration of homeostasis in the CNS. Neurons may inactivate immunocompetent cells by several mechanisms dependent on cell-cell contact or the secretion of soluble factors such as neurotrophins and neurotransmitters [3,16,31]. The balance between the induction and inhibition of several types of cells allows brain parenchyma remodelling and rebuilding following brain injury.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that this discrepancy is likely due to intracellular signaling mechanisms for PICs to play a role. A great deal of evidence has demonstrated that IL-1β and TNF-α play a role mainly via p38 MAPK, ERK and JNK signaling transduction pathways, but IL-6 plays a role via JAK-STAT pathways [27][28][29]. After activation of those signaling pathways, gene transcription occurs [30][31][32].…”
Section: Discussionmentioning
confidence: 99%